2017 14th International Conference on the European Energy Market (EEM) 2017
DOI: 10.1109/eem.2017.7981953
|View full text |Cite
|
Sign up to set email alerts
|

The end of long-term contracts? Gas price and market dynamics in Central and Eastern Europe

Abstract: This paper analyses the development of natural gas prices in Central and Eastern Europe (CEE) and assesses its drivers. Furthermore, the relation to recent changes in import contracts is discussed. The methodological approach consists of a panel analysis, in which wholesale gas prices in CEE countries are explained by a set of exogenous drivers, and a descriptive part on changes in contracts. The results provide evidence that a decreased share of oil-indexed long-term contracts has significantly reduced gas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, one cannot lose sight of the direct relationship between oil and gas prices (despite lower importance of oil-indexed long-term contracts that decreased gas prices for CEE, [13]) and the fact that when they reach a certain level there is a significant change in their share in the European energy consumption basket, which has both positive and negative impacts. Nevertheless, there has been changing, challenging the established trading principles of Russian gas in EU recently [14].…”
Section: Resultsmentioning
confidence: 99%
“…However, one cannot lose sight of the direct relationship between oil and gas prices (despite lower importance of oil-indexed long-term contracts that decreased gas prices for CEE, [13]) and the fact that when they reach a certain level there is a significant change in their share in the European energy consumption basket, which has both positive and negative impacts. Nevertheless, there has been changing, challenging the established trading principles of Russian gas in EU recently [14].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the empirical model, Wachsmuth et al (2017) analyzed the development of natural gas prices and discussed the changes of import contracts in Central and Eastern Europe (CEE). It was found that a decreased share of oil-indexed long-term contracts had significantly cut down the gas prices in Central Europe.…”
Section: Frontiers In Earth Sciencementioning
confidence: 99%
“…Developments in the EU gas market proved that gas-on-gas pricing prevails, and oil indexation is phasing out in contracts, despite the strong opposition of Gazprom and its reluctance to change. The change in contract pricing of the Russian contracts was to a large extent enforced by arbitration court decisions (Mitrova, et al, 2015;Neumann, et al, 2015;von Hirschhausen, et al, 2020;Wachsmuth, et al, 2017).…”
Section: European Commission As a Watchdog On Fair Competitionmentioning
confidence: 99%